The use of live yeast suspensions in beef cattle rations. - Baker, F.H.; Richardson, D.; Harris, J.O.; Cox, R.F.; Bowman, O.M. (Kansas Agricultural Experiment Station, 2011)
Forty head of choice-quality steer calves were used in the wintering phase of this test. These calves were part of a shipment from the Lonker Ranch, Medicine Lodge, Kan. The steers were assigned to lots on the basis of weight and feeder grade, The live yeast suspensions used in this experiment are Torula utilis and Saccharomyces cerevisiae. The yeast suspensions were prepared weekly and stored at the optimum temperature until fed. They were prepared to supply 3 billion live yeast cells per animal daily. The suspensions were mixed with ½ pint of water and sprinkled over the rations in the feed bunks each morning. Results of this phase of the study are presented in Table 51. A digestion study was conducted to determine the influence of the two strains of yeast on the digestibility of a cattle-fattening ration composed of 3 parts milo grain and 1 part alfalfa hay. Eleven yearling Hereford steers weighing 700 pounds each were used in this study.
Keywords: Beef; Live yeast; Digestibility; Gain; Feed efficiency